2015
DOI: 10.3923/rjes.2015.193.199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prevalence of Pediculosis capitis among Primary School Girls in Riyadh, Saudi Arabia

Abstract: The prevalence of Pediculosis capitis human head lice, among children is a worldwide public health alarm. The study aimed to assess the prevalence of head lice and associated risk environmental and personal factors among primary school girls. Study sample included 590 students from different primary school grades. The results showed that (12.2%) 72/590 of students were infected with Pediculosis capitis. A high rates of infestation was observed among students, who had a long hair, poor family and illiterate mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
2
Order By: Relevance
“…In the case of refugees, most of the crowded families were living together in resident place and they are using same things. Some studies found low or no significant correlation between lice infestation and the size of the family in contrast to this result [27,9].This study also shows the frequency of hair washing affected lice infestation significantly. This is compatible to [28] in Ravansar west of Iran, they found a significant relationship between infestation and hair washing frequency.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In the case of refugees, most of the crowded families were living together in resident place and they are using same things. Some studies found low or no significant correlation between lice infestation and the size of the family in contrast to this result [27,9].This study also shows the frequency of hair washing affected lice infestation significantly. This is compatible to [28] in Ravansar west of Iran, they found a significant relationship between infestation and hair washing frequency.…”
Section: Discussioncontrasting
confidence: 49%
“…Also, some studies which reported that hair length did not appear to be an independent risk factor [29]. However, other studies found that long-haired girls were more infested with lice [25,27]. The findings can be attributed to the fact that most of the refugees because of their method of life have no long hair and most of them the hair characters are similar.…”
Section: Discussioncontrasting
confidence: 44%
“…The prevalence of pediculosis capitis in this study was 68.7% of children in primary schools infested with head lice. This prevalence is quite high compared to studies reported recently in several places, 2.01% in the European Union [26], 12.2% in Riyadh, Saudi Arabia [21], 10% in Barat Daya Iran [25] and 44% in Batambang, Cambodia [27]. Respondents from the researches mentioned previouslty were generally elementary school children in urban areas, where as this research was conducted in rural areas.…”
Section: Discussionmentioning
confidence: 54%
“…In rural areas, pediculosis capitis was reported to be higher by a number of earlier studies [26]. Megrin [21] had point out that area of residence contributes significantly to the rate of head lice infestation in children (19,2%, p < 0.001). A study conducted at Sabang city, Province of Aceh Indonesia, reported that urban account for 26,6 % prevalence of pediculosis capitis compared to 27.1% of children with infestation of pediculus capitis in rural area [28].…”
Section: Fig-1: Kawiley Vilage (Rignolda Djamaluddin)mentioning
confidence: 88%
See 1 more Smart Citation